Edukasi Golongan Obat Bebas dan Obat Bebas Terbatas Pada Siswa Kelas 12 Di Pandeglang Banten - Candra Junaedi; Ucu Mawardi; Dimas Danang Indratmoko (Universitas Muhammadiyah Manado, 2022)
Public knowledge of drugs is quite limited, especially among teenagers. Adolescence is a developmental change between childhood and adulthood that results in physical, cognitive, and psychosocial changes. The aim of this education is the early introduction of over-the-counter drug classes to teenagers so that awareness is formed regarding the proper and correct use of over-the-counter drugs. The activities were conducted on class 12 students at SMA Mathlaul Anwar Pandeglang Banten. Educational facilities use leaflets that are distributed to activity participants. Evaluation of participants was carried out by asking for answers and filling in pre-test and post-test questions regarding education on the use of over-the-counter drugs. The results of education on the introduction of over-the-counter non-restricted medicines before and after schooling can increase teenagers' knowledge about self-medication over-the-counter drugs, especially adequate information regarding the correct use of drugs, including indications, dosage, method of use, side effects, contraindications, and drug expiration dates.